2008
DOI: 10.1016/j.tem.2008.07.005
|View full text |Cite
|
Sign up to set email alerts
|

ERRα: a metabolic function for the oldest orphan

Abstract: Estrogen receptor related receptor (ERR)α was one of the first identified (1988) orphan nuclear receptors. Many of the orphan receptors identified after ERRα were deorphanized in a timely manner and appreciated as key transcriptional regulators of metabolic pathways. ERRα, however, remains an orphan. Nevertheless, recent studies have defined regulatory mechanisms and transcriptional targets of ERRα, allowing this receptor to join ranks with other nuclear receptors that control metabolism. Notably, mice lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
207
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 225 publications
(215 citation statements)
references
References 68 publications
6
207
0
2
Order By: Relevance
“…S3B). As predicted based on studies of ERRα function in other tissues (20,21), gene ontology analysis identified genes broadly involved in metabolic processes ( Fig. S3 C and D).…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…S3B). As predicted based on studies of ERRα function in other tissues (20,21), gene ontology analysis identified genes broadly involved in metabolic processes ( Fig. S3 C and D).…”
Section: Resultsmentioning
confidence: 60%
“…Consistent with reduced activation and differentiation of ERRα −/− T cells, stimulation of CD4 + T cells isolated from naive 6-to 8-wk-old ERRα −/− mice resulted in decreased CD44 expression after 24 h (Fig. 1D) and reduced production of IL-2 and IFN-γ ( ERRα associates with the coactivators peroxisome proliferatoractivated receptor-γ coactivator-1α/β (PCG1α/β) to regulate multiple metabolic pathways (20,21) and may link lymphocyte metabolism and function. As CD4 + T cells were also found to express PCG-1β (Fig.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations